Pengaruh Return On Asset Terhadap Nilai Perusahaan Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Krisnando . (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
This study is aimed to test the effect of return on assets on firm value with managerial ownership as a moderating variable in manufacturing companies that listed in Indonesia Stock Exchange (BEI) with the research period from 2016 to 2017.This research uses associative quantitative approach, which is measured using of multiple linear regression based method use Eviews 9. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016 up to 2017. Sample was determined by purposive sampling method, and get 61 manufacturing companies. So, total observation in this research are 122 observations. The data used in this study are secondary data. Data collected techniques using the documentation method through the official website of IDX: www.idx.co.id, hypothesis testing are using t test.The results of the study prove that (1) Return on Assets has a significant positive effect on Company Value which is proxied by Tobin's Q on manufacturing companies listed on the IDX for the period 2016-2017, (2) Managerial ownership does not significantly influence or weaken the relationship between Return on Assets with Company Value which is proxied by Tobin's Q for manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2017